Solar irrigation for adapting to climate change in cocoa farming: a choice experiment approach identifying Ghanaian farmers’ preferences - Gbodji, Kekeli Kofi; Quarmine, William; Buisson, Marie-Charlotte; Mitra, Archisman; Schmitter, Petra (Elsevier, 2026)
Future climate conditions will be characterized by substantial uncertainty in weather patterns. For cocoa production, adapting to climate change will require securing water application and soil moisture by investing in irrigation infrastructure. In Ghana, government and private sector organizations have introduced solar-powered groundwater irrigation solutions to address the challenges. However, high upfront costs, limited access to institutional finance, and hydro-geological uncertainties constrain demand. We employed a discrete choice experiment approach to examine cocoa farmers’ willingness to adopt solar-based irrigation, surveying 550 farmers across seven regions depending on type of ownership, incentivized loans, and cutbacks on drilling uncertainties. The study revealed that cocoa irrigation investment decision depends primarily on access to longerterm loans, followed by cost reduction through group ownership, with the last factor being the reduction of uncertainties associated with borehole drilling. However, there are differences in farmers’ stated preferences based on wealth resources, gender, farm access, cocoa farm size, and household size. These findings suggest that policymakers should prioritize initiatives that alleviate financial constraints through longer-term loans to promote climate-resilient and sustainable agriculture. In addition, it indicates that a one-size-fits-all approach to promoting solar irrigation investment is unlikely to be effective, due to substantial heterogeneity in preferences amongst farmers. Instead, targeted policies are needed to increase solar pump adoption among marginalized groups like women and resource-poor farmers.